Differential diagnosis of leukemia by immunophenotyping (Research, Society and Development, 2022)
Introduction: the hematopoietic process is of immense importance for the organism, as it is responsible for the formation of hematological cells. However, errors in this phase can generate cells that are unable to perform their functions and trigger pathologies, such as a leukemic condition. Leukemia is defined as a malignant neoplasm (cancer) that can affect all age groups and its origin is usually unknown. This disease is classified according to the degree of cell maturation and the affected lineage, thus, it can be acute or chronic and myelocytic (when the affected lineage is the myeloid) or lymphocytic (when the lymphoid lineage is compromised). The diagnosis can be made by several tests, but immunophenotyping is considered the gold standard due to its high specificity and sensitivity. Objective: to characterize the different leukemic processes (myeloid and lymphoid, acute and chronic) and their peculiarities, to explain the importance of differential diagnosis by the immunophenotyping method and how it is performed. Methods: data from the Scientific Electronic Library Online (SCIELO), Google Scholar, PubMed and other articles found in virtual scientific journals were used. Conclusion: the time that the diagnosis of leukemia is performed is of paramount importance, this will interfere with the entire treatment and prognosis and the main method that should be used is immunophenotyping.